1997
DOI: 10.1038/sj.sc.3100548
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar cerebrospinal fluid pulse wave rising from pulsations of both the spinal cord and the brain in humans

Abstract: There are two theories regarding the origin of the lumbar cerebrospinal¯uid pulse wave (L-CSFPW): that it arises from the arteries supplying the spinal cord, and that it is due to the pulsations of the brain transmitted through the subarachnoid space of the spine.We investigated L-CSFPW of 11 myelopathic patients with a complete (®ve patients, CBgroup) or an incomplete spinal block (six, ICB-group) on myelography to determine the origin of L-CSFPW. Since arterial pressure amplitude (APA), the energy source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…However, in the real anatomy spinal arteries connect to the cardiovascular system not only through the vertebral anastomosis but also directly from arteries such as the radicularis magna branching from the aorta [35], so arterial blood flow is not limited to the rostrocaudal direction and neither is venous return. This branched network of blood vessels will provide distributed excitation to the SC tissues as well as the fluid and surrounding tissues of the SSS, all of which will contribute to the spinal CSF pulse wave, as will CSF pulsations transmitted from the head [6,[9][10][11]. In simulations where c Vasc,SC was changed from zero in increments up to c Vasc,SSS the main effect was a phase shift of p (not shown).…”
Section: Limitations Of the Current Workmentioning
confidence: 86%
See 1 more Smart Citation
“…However, in the real anatomy spinal arteries connect to the cardiovascular system not only through the vertebral anastomosis but also directly from arteries such as the radicularis magna branching from the aorta [35], so arterial blood flow is not limited to the rostrocaudal direction and neither is venous return. This branched network of blood vessels will provide distributed excitation to the SC tissues as well as the fluid and surrounding tissues of the SSS, all of which will contribute to the spinal CSF pulse wave, as will CSF pulsations transmitted from the head [6,[9][10][11]. In simulations where c Vasc,SC was changed from zero in increments up to c Vasc,SSS the main effect was a phase shift of p (not shown).…”
Section: Limitations Of the Current Workmentioning
confidence: 86%
“…The cardiac cycle sets up a spinal CSF pulse wave, generated by spinal arterial pulsations, spinal venous pulsations and the intracranial CSF pulse wave transmitted through the spinal canal [6,[9][10][11]. The relative contributions of these sources is a moot point though; a study using direct pressure measurements on canines placed the values at approximately 40%, 40% and 20%, respectively [9], while a phase-contrast MRI study on humans suggested that the intracranial CSF pulsations may play a more prominent role [6].…”
Section: Introductionmentioning
confidence: 99%
“…SOT can evaluate the condition of meningeal tension (3,4,6,7,9) which is associated with the flexion/inhalation and extension/exhalation phase of the primary respiratory motion. When the meninges, neural tissues, and specifically the spinal dura are fixated in flexion or extension it is theorized that this could affect lumbar cerebrospinal fluid fluctuations (3,(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of the parameters are as follows: stroke volume (mL); average of the CSF volume moving caudally during systole and cephalically during diastole, regurgitant fraction (%); the ratio of caudal to cranial flow of the CSF per single stroke volume, absolute stroke volume (mL); the integral over time for the volumetric flow rate, and flux (mL/s); "mean velocity ϫ area" or the CSF volume that passes the contour per second. 11,12,19 Two radiologists, who were blinded to the aims of this study, manually placed circular ROIs in triplicate at different sessions for each sample, respectively, and obtained the mean values of the circular ROIs. Analysis and data post-processing were performed at a workstation, and the measured signal changes were converted to a velocity, and the amount of flow was determined using an analysis program (View Forum, Philips Medical System, Best, The Netherlands).…”
Section: Mri Studymentioning
confidence: 99%
“…9 -11 In addition to this pump flow mechanism, spinal vascular pulsations are considered to be the origin of spinal CSF pulsation in more complex ways. 8,12 We hypothesized that the rapid prehydration of relatively large amounts of crystalloid would affect the physical properties of the CSF such as flow and oscillatory motion which, in turn, would influence the spread of local spinal anesthetics in the intrathecal space. A two-stage study was designed to test this hypothesis.…”
mentioning
confidence: 99%